A Comparative study of copy-move forgery detection methods. (April 2020) - Agarwal, Ritu; Verma, Om Prakash
Abstract: Images hold a major influential power, as evidence or as a medium to convey messages. An image is worth a thousand words and is used extensively in this era for digital communications. Hence, their tampering can cause major losses, which is why their manipulations techniques have grown sophisticated over time. Copy-move forgery is a technique, wherein an area of an image is replicated to another area of the image. The paper reviews state of the art copy-move forgery detection (CMFD)methods listing the approach and limitations of various techniques with the help of a table for better readability.